Sacred Spaces of New England: Artistic Research, Cultural Heritage, and Virtual Reality Panoramic Photography - Thompson, Seth (2020)
Artistic research is a methodology that integrates artistic activities within either the research process or its outcomes. By using New England's sacred spaces as a case study for the documentation and interpretation of cultural heritage, this paper provides an overview of the author's ongoing Sacred Spaces of New England project, examines how New England's sacred spaces are increasingly becoming "at-risk" heritage sites, and considers the value of documenting and mapping them using virtual reality panoramic photography and associated technologies.